Local delivery systems of morphogens/biomolecules in orthopedic surgical challenges. (June 2021) - Roy, Subhasis; Mukherjee, Prasenjit; Das, Pradip Kumar; Ghosh, Prabal Ranjan; Datta, Pradyot; Kundu, Biswanath; Nandi, Samit Kumar
Graphical abstract: Abstract: Musculoskeletal disorders and bone deficiencies have been established among the most important human health conditions that exist today. Because of the numerous and complex functions of bone, there are many disorders, such as osteoarthritis, rheumatoid arthritis, osteoporosis and bone cancer that arise with time. Conventional therapy alone does not always yield satisfactory results and the treatment protocol is difficult, time consuming and expensive. Systemic therapy has the disadvantages of the need for long-term treatment due to being unable to create a high local concentration and the resultant risk of toxicity in addition to problems of drug transport and cost. As a result, intensive research activity on targeted local delivery of drugs/growth factors has been initiated. Local drug delivery is potentially an advantage over standard oral/intravenous therapy/other modalities. In the present review, we have highlighted various drugs/growth factors/molecules and their potential local delivery systems for effective management of bone disorders.